(untitled) (Applied Biological Research, 2024)
Malaria is still a global concern with around 214 million annual cases and 430,000 annual deaths, mainly among of children younger than 5. Now a days people mostly dependent on the herbal based remedies to cure this type of diseseases and currently most preferred therapy is artemisinin combination therapy (ACT). The genus Artemisia annua L., one of the largest genera belonging to the Compositae family consisting of more than 350 species. One important tool for creating unique genetic variation in crops, functional genomics, and breeding is the use of chemical mutagens. They are useful since they can cause a high mutation frequency and don’t need any specialist equipment. Chemical mutagens produce point mutations as opposed to deletions or translocations as compared to physical techniques. Point mutations can affect gene expression in a variety of ways, from knockouts to modifications in amino acids that may have a minor impact on the function of proteins. The experimental procedure for induced EMS mutagenesis, Williams et al. was followed and triple technical repeats of three different percentages of EMS (Ethyl methane Sulphonate) doses (0.10%, 0.30%, 0.50%) and a control dose (0% EMS) were applied. the process of screening mutants frequently revealed the presence of several allelic mutants generated by EMS. Present study resultant displayed that EMS lower doses will prove to be a revolutionary mutant for creating new variation as EMS mutagenesis enables cost-effective and high-throughput generation of mutations, greatly accelerating plant genomes research and facilitating the advancement of molecular breeding for plants with enhanced tolerance to abiotic stress.